Pertimbangan dan Sensus Communis. Revolusi Kopernikan dalam Pemikiran Politik Arendt: Judgment and Sensus Communis. The Copernican Revolution in Arendt’s Political Thought - Fitzerald Kennedy Sitorus (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2026)
This article discusses Arendt’s political philosophy, which she developed by interpreting Kant’s aesthetics. Through a hermeneutic reconstruction of Arendt’s texts, the author shows how she interprets and uses two of Kant’s aesthetic concepts, i.e., judgment and sensus communis, as the basis for political philosophy. The result is a political anthropology grounded in sensus communis. For Arendt, politics is the manifestation of sensus communis. Humans become zoon politicon because they possess the a priori faculty of sensus communis, which is a condition for the possibility of politics. Arendt’s political philosophy is still relevant because it reveals and reminds us of something important: the decline of sensus communis—or the dimension of shared judgment among citizens—becomes the condition for the emergence of totalitarian regimes. In the age of digital media dominance, which is eroding our sensus communis and pushing people apart, Arendt’s warning is more important than ever. We must nurture and develop sensus communis through communication, dialogue, and the exchange of ideas. This is how we can understand each other and find common ground in our political lives. Abstrak Artikel ini membahas filsafat politik Arendt yang dibangun melalui interpretasi atas filsafat keindahan (estetika) Kant. Melalui metode rekonstruksi hermeneutis atas teks-teks Arendt, penulis memperlihatkan bagaimana Arendt menafsirkan dan menjadikan dua konsep pertimbangan estetis Kant, yakni pertimbangan (judgment) dan sensus communis, sebagai fondasi filsafat politik. Hasilnya adalah sebuah antropologi politik yang didasarkan atas sensus communis. Politik bagi Arendt adalah manifestasi sensus communis. Manusia menjadi zoon politikon karena dalam dirinya sudah terdapat fakultas apriori sensus communis sebagai syarat kemungkinan politik. Filsafat politik Arendt tetap aktual karena dapat memperlihatkan sekaligus mengingatkan kita: kemerosotan sensus communis atau dimensi pertimbangan bersama antar-warga negara menjadi kondisi bagi kemunculan rezim totaliter. Di tengah dominasi media digital dewasa ini, yang menggerus sensus communis kita dan membuat orang teralienasi satu sama lain, peringatan Arendt penting: kita harus tetap memelihara dan mengembangkan sensus communis melalui komunikasi, dialog dan pertukaran pikiran agar dapat saling memahami dan mencari orientasi bersama dalam kehidupan politik. Kata-kata Kunci: pertimbangan, sensus communis, politik, imajinasi, refleksi, totalitarianisme